Compliance with IMF Program Indicators and Growth in Transition Economies - Unigovskaya, Anna.; Mercer-Blackman, Valerie (Washington, D.C. : International Monetary Fund, 2000)
This paper makes use of the IMF's Database for Monitoring Fund Arrangements (MONA) to investigate whether transition countries that more successfully implement the conditionality of IMF programs tend to show a better performance on recovery and growth. It is not possible to determine a clear-cut relationship between the index that determines the level of compliance with structural benchmarks in IMF programs and growth. However, the paper finds a definite, positive relationship between the index of compliance with performance criteria and growth, even after controlling for the extent of stabilization of the transition countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country; Fund Program; Performance Criteria; Transition Economy; WP; Bulgaria